REVIEW OF THE STATE OF KNOWLEDGE OF CENOZOIC BIVALVES FROM THE RUSSIAN FAR EAST - Kafanov A.I. (My University, 2003)
By the beginning of the 21st century, 1227 species and subspecies of marine and brackish-water bivalves, assigned to 225 genera and subgenera of 54 families, were described from the Cenozoic of the Russian Far East by Russian, Japanese, and American paleontologists. Of these species and subspecies, 793 are valid taxa, 163 are nominal (nomenclatorially suitable) taxa, whose accurate taxonomic attribution is so far problematic, and 271 taxa are described in open nomenclature as "cf.," "aff.," "ex gr.," etc.; 157 species and subspecies are synonymized under other taxa. Analysis of the state of taxonomic and stratigraphical knowledge and the main directions for future research are given.
Keywords: Cenozoic; Cenozoic; Кайнозой